The Association between Participation in Fights and Bullying and the Perception of School, Teachers, and Peers among School-Age Children in Serbia - Sanja Stankovic; Milena Santric-Milicevic; Dejan Nikolic; Nenad Bjelica; Uros Babic; Ljiljana Rakic; Zorica Terzic-Supic; Jovana Todorovic (MDPI AG, 2022)
Participating in physical fighting and bullying can be a cause of severe injury and death among school-age children. Research evidence can support school and health actors' efforts to improve school-age children's development and health capacity for life. The study aims to assess the prevalence of school-age children's participation in fights and bullying in Serbia, and to examine the relevance of students' socio-demographic characteristics and perceptions of school and relations with other students and professors for participation in fights and bullying. A secondary analysis is also performed on the original data of the 2017 HBSC study, which was conducted on 3267 students in a nationally representative sample of primary and high schools in Serbia. We sought to investigate the relationship between eight socio-demographic characteristics and nine school-related perceptions, with two outcome variables: taking part in fights and taking part in bullying, examined by using univariate and multivariate logistic regression. The main results show that 50.8% of boys and 17.1% of girls have taken part in fights, while 17.7% boys and 10.4% of girls have taken part in bullying. Students who felt a large and very large burden of school obligations were 1.43 times more likely to participate in bullying at least once, while they were 1.38 and 2.12 times more likely to participate in multiple fights and 4.04, 1.24, and 2.78 times more likely to participate multiple times in bullying. Multiple participation in fights and in bullying is significantly negatively associated with female gender, younger age years, good and very good perception of family financial status and quality of life, and positive perceptions of school and relations they have with other students and professors. Fights among school-age children are significantly positively associated with living with relatives/legal guardians and poor quality of life. In conclusion, the prevalence of participating in at least one fight/bullying is higher than in multiple fights/bullying. These associations suggest a necessity to enhance the monitoring and control of peer behavior among school-age children. The findings of the study imply key enablers of protection, such as building relationships based on team spirit and work, friendly behavior, empathy, and help, which should be included in the value system of school and family activities in programs to combat fights and bullying in school-age children.